Огляд типів машинного перекладу - Павленко, О. С. (ХНУРЕ, 2024)
Nowadays, there is a wide variety of information available in many languages. In order for people from different parts of the world to be able to watch and understand any video without any problems, regardless of language, translation is needed. Automatic generation and translation of subtitles became the best solution to this problem. After speech is transcribed into text, it needs to be translated, and translation needs to be both fast and accurate. The purpose of this article is to analyze machine translation methods and determine which one is best suited for real-time subtitle translation.
Keywords: машинний переклад